Short fiber reinforced elastomeric composites with enhanced mechanical and tribological properties for potential application in V-belts - Gupta, Piyush; Chattopadhyay, Santanu; Das, Narayan Chandra (Frontiers in Mechanical Engineering, 2025)
The effect of aramid short fibers on the cure characteristics, processing behaviour, as well as the physical and mechanical properties of ethylene-propylene-diene terpolymer rubber (EPDM) is investigated. The EPDM rubber is reinforced with hybrid fillers like aramid fibers, silica, and carbon black while undergoing peroxide vulcanization. Masterbatches are prepared using an internal mixer while keeping different fiber percentages such as 2, 4, 6, 8, 10, 12, 15 and 20 phr. Then, the impact of these different fiber percentages on the viscoelastic, mechanical and dynamic properties of the base rubber of the V-belt is studied; the results indicate that viscosity, maximum–minimum torque, and cure rate were increased by adding fiber, the fiber content has a great influence on the mechanical properties as well. At 6 phr fiber loading, the tensile strength decreased slightly to 18.76 MPa, elongation at break reached 413.4%, tear strength improved to 76.2 kgf/cm, and abrasion loss dropped to 61.1 mm3—demonstrating an excellent equilibrium of strength, flexibility, and wear resistance. The introduction of fibers decreased resilience and flexibility (which led to poorer results in flex testing for high-concentration fiber-reinforced composites). Heat build-up and compression set were increased with fiber concentration for the composites. From the De-Mattia Fatigue Study, it is clear that 6 phr of fiber concentration shows the best fatigue life, in which the crack initiates after 367 kilocycles, which is the highest among all, and full rupture of the specimen occurs at 545 kilocycles. The crack growth resistance test indicated that the 6 phr fiber-filled sample possessed very little crack extension: only 4 mm after 10,000 cycles and 13 mm after 25,000 cycles. This shows that the specimen with 6 phr is most resistant to fracture development. This research allows for the development of rubber composites with precisely controlled mechanical properties for demanding engineering uses. In addition, it provides a valuable benchmark for future investigations of alternative fiber reinforcement, especially natural ones. A better understanding of the fundamental principles of tension, tear, and wear in such compounds can lead to the design of more sustainable materials due to their extended lifespan.